2021
DOI: 10.3390/microorganisms9020340
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Characterization of Campylobacter fetus subsp. venerealis Strains

Abstract: The pathogenesis mechanisms of Campylobacter fetus subsp. venerealis (Cfv), the etiologic agent of Bovine Genital Campylobacteriosis remain elusive. This study evaluated the virulence potential and biovar characteristics of Cfv isolates (n = 13) by PCR screening of putative virulence-factor (VF) genes, Multilocus Sequence Typing (MLST) analysis, antimicrobial susceptibility to tetracycline, penicillin, enrofloxacin and streptomycin testing and whole-genome sequencing (WGS; n = 5), also comparing the latter wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Five antibiotic resistance ontologies (AROs) likely underlie the multidrug resistance of Shenzhen WH 0221 ( Table 6 ). Efflux pump proteins and related genes are kdpE ( 20 ), ykkD ( 21 ), and cmeB ( 22 ), potentially explaining resistance to aminoglycoside, phenicol, cephalosporin, and fluoroquinolone antibiotics. TLA-3 is a β-lactamase ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five antibiotic resistance ontologies (AROs) likely underlie the multidrug resistance of Shenzhen WH 0221 ( Table 6 ). Efflux pump proteins and related genes are kdpE ( 20 ), ykkD ( 21 ), and cmeB ( 22 ), potentially explaining resistance to aminoglycoside, phenicol, cephalosporin, and fluoroquinolone antibiotics. TLA-3 is a β-lactamase ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…That study also reported differences in pregnancy rates in infected cows, being higher in Cfvi than in Cfv . Although genomic differences between Cfv and Cfvi have been identified [ 29 ], further studies are needed to determine which pathogenicity genes could be directly related to these differences in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these genes was previously reported to be rare in C. jejuni and C. fetus subsp. venerealis isolates worldwide ( Bacon et al, 2000 ; Panzenhagen et al, 2021 ; Silva et al, 2021 ). A mutation in virB11 was also shown to reduce C. jejuni 81–176 adhesion and invasion by 6- and 11-fold, respectively compared to wild-type ( Bacon et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%